Problematika Tindak Pidana Pelecehan Seksual Terhadap Laki-Laki: Bahasa Indonesia - Khazza Kayvana Affadya; Aji Lukman Ibrahim (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Abstract : This study aims to discuss sexual harassment against men, which in the last few years has continued to increase and is troubling so that it can be categorized as a problem that needs to be addressed immediately. Various factors such as toxic masculinity and gender double standards can be one of the causes of rampant sexual harassment against men, especially in Indonesia. All forms of regulations that have been passed and enforced have not been able to provide a significant direct effect in reducing the number of sexual harassment that occurs to men. This happens because good regulations are not accompanied by good implementation by law enforcement officials and the lack of participation and concern from the community in responding to the seriousness of sexual harassment against men. It is hoped that special spaces, institutions and forums that need to be provided to provide a greater sense of security for male victims of sexual harassment can be realized immediately in order to overcome the current problems. The writing of this research uses a normative method with several approaches, namely the statutory approach, the conceptual approach, and the case approach. The results of this study are expected to provide theoretical benefits in the form of scientific development in the field of criminal law, especially those concerning sexual harassment in men and practical benefits in the form of new insights for writers and readers, including input for the government, law enforcement officials in taking steps appropriate and efficient policy steps to uphold fair and balanced legal protection to reduce or prevent the occurrence of criminal acts of sexual harassment against men. Keywords: Sexual Harassment, Male Victims, Law Enforcement